Fertility restoration studies in different cytoplasms of pearl millet [Pennisetum glaucum (L.) R. BR.] - Amiribehzadi, Alidad; Satyavathi, C. Tara (Annals of Agricultural Research, 2014)
Pearl millet [Pennisetum glaucum (L.) R. Br.], hybrids grown widely in India are all based on A1 CMS source. Though alternative sources of CMS are available and found to be highly stable, their utility is restricted due to non-availability of suitable restorers. The present investigation carried out using three different cytoplasms (A1, A4 and A5) as female and A1 cytoplasm as male showed differential restoration of fertility. The fertility restoration was moderate to partial for both A4 (16% to 52%) and A5 (20%) cytoplasms. The male parent PPMI 69 showed complete fertility restoration with ICMA 99555 belonging to A4 cytoplasm. Identification of restorers for diverse cytoplasmic male sterile sources opens up new avenues in pearl millet hybrid breeding.